A Medicine Stock Management System of an Agrobusiness Company Using Barcodes - Hong Yun, Lim; Ab. Aziz, Ruhaya (Applied Information Technology And Computer Science, 2022)
In this project, a web-based medicine stock management system is designed, developed and tested to improve the medicine stock management of an agrobusiness company called Leong Hup Agrobusiness Sdn. Bhd. The current medicine stock management of the company is via manual paper recording and has caused some problems such as data recording errors. The development of the system is driven by the prototyping software process model. Using the system, the users can manage the medicine stock more efficiently with the aid of digital computer technology. Also, the barcode is used to identify the medicine making stock identification easier. Lastly, testing is done to ensure the system meets the requirements. The medicine stock management system is expected to improve the efficiency of medicine stock management for the company.